Comparison Of Student’s Self Esteem With High Learning Achievement And Low Learning Achievement In Junior High School - Siti Warniyanti; Indra Ibrahim (Jurnal Neo Konseling, 2019)
This research is motivated by the phenomenon of students who have high learning achievement and low learning achievement, who have a lack of trust with their abilities, feel pessimistic, doubtful, lack of confidence, easily offended when disagreeing with others, doing denial and run away from problems if they make mistakes with their friends, are not satisfied with their learning achievements. This relates to students' self esteem and their learning achievement. This study aims to: (1) describe the self esteem of high learning achievement and low learning achievement students, (2) compare of student’s self esteem who have high learning achievement and low learning achievement students.This research uses quantitative methods with with a comparative descriptive type. The population of this study were 848 students of SMPN 13 Padang. The total sample of 238 students was selected using the Purposive Random Sampling technique. The research instrument used was an self esteem questionnaire for students. Data were processed using descriptive statistical analysis and analysis of t-test techniques.The results of the study revealed the self esteem of students on; (1) Self Esteem of student’s with high learning achievement is in the high category, (2) Self Esteem of student’s with low learning achievement is in the high category, (3) there are differences which is significant regarding the self esteem of high learning achievement and low learning achievement students.